2020
DOI: 10.1108/pr-07-2019-0404
|View full text |Cite
|
Sign up to set email alerts
|

The future of your job represents your future: a moderated mediation model of transformational leadership and job crafting

Abstract: PurposeIn this study, the authors aim to explain the mechanism between transformational leadership and job crafting. They predict that job-based psychological ownership (job-based PO) mediates the relationship between transformational leadership and job crafting. Furthermore, job-based PO is more effective when employees have a high level of affective organizational commitment.Design/methodology/approachThe authors collected time-lagged data through a paper–pencil survey from the sales department of large phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 79 publications
1
26
0
Order By: Relevance
“…Job-based psychological ownership is an attitude towards jobs with both affective and cognitive elements (Hameed et al, 2019;Pierce et al, 2001Pierce et al, , 2003 and creates a psychological linkage between an employee and his/her job (Naeem et al, 2020). Employees with higher jobbased psychological ownership tend to take higher responsibility for their jobs and try to Roles of shared leadership protect and enhance their ownership of jobs (Pierce et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Job-based psychological ownership is an attitude towards jobs with both affective and cognitive elements (Hameed et al, 2019;Pierce et al, 2001Pierce et al, , 2003 and creates a psychological linkage between an employee and his/her job (Naeem et al, 2020). Employees with higher jobbased psychological ownership tend to take higher responsibility for their jobs and try to Roles of shared leadership protect and enhance their ownership of jobs (Pierce et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Affective commitment covers the basic psychological needs of individuals, which can induce them to restructure their work. Affective commitment fosters employees' sense of attachment, identification with the organization, and belonging to it, which can fuel their motivation for job crafting [15]. Commitment is an integral socio-psychological attitude, formed as a combination of loyalty, engagement and identification [16].…”
Section: Methodsmentioning
confidence: 99%
“…However, we did not further explore the mechanism by which affective commitment affects job boredom. Previous studies have shown that employees with high affective commitment could carry out more job crafting (Naeem et al, 2021), which, in turn, reduces job boredom . Future research could further explore the mediating mechanism between affective commitment and job boredom.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%